Chinese Medicine, Acupuncture and Science - Peter Eckman; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. Ever since the introduction of Western biomedicine into China, there has been friction between proponents of this new approach, and proponents of the traditional medical practices that had evolved over thousands of years in China. For the most part, this friction has been couched in the unexamined assumption that Western medicine is based on science, while Chinese medicine is not. This article will examine that assumption, which in this author's opinion is unjustified and incorrect. Having practiced acupuncture for the past 50 years, after receiving my doctoral degrees in medicine and physiology, my thinking on this topic has also evolved over time. I will begin this article with some historical information that bears on the topic under discussion, followed by my personal ideas about how to resolve the conflicts that have arisen.